Pengaruh Penghindaran Pajak, Perencanaan Pajak, dan Struktur Modal Terhadap Nilai Perusahaan - Noviana, Martia Nur; Afridayani, Afridayani (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
This study aims to provide empirical evidence on the influence of Tax Avoidance, Tax Planning, and Capital Structure on Firm Value in the consumer non-cyclical sector listed on the Indonesia Stock Exchange (IDX) during the period 2019–2024. This sector was selected due to its relatively stable performance and significant contribution to the national economy, making it relevant for examining the relationship between tax management strategies and firm valuation. The research adopts a quantitative approach using purposive sampling. Based on predetermined criteria, a total of seven companies were selected as the sample, resulting in 42 observations over a six-year period. Panel data regression analysis was employed to examine the effect of the independent variables—Tax Avoidance (X1), Tax Planning (X2), and Capital Structure (X3)—on the dependent variable, Firm Value (Y). The findings indicate that, simultaneously, all three independent variables have a significant effect on Firm Value, suggesting that the combined impact of tax strategies and financing decisions plays an important role in shaping market perceptions. Partially, Tax Avoidance shows a significant positive influence on Firm Value, implying that efforts to reduce tax burdens are perceived favorably by investors. Conversely, Tax Planning and Capital Structure do not exhibit significant individual effects. These results provide valuable insights for companies and investors regarding the importance of effective tax management strategies in enhancing firm value.